2020
DOI: 10.3390/electronics9020340
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor Using a One-Port Interdigital Capacitor: A Resonance-Based Investigation of the Permittivity Sensitivity for Microfluidic Broadband Bioelectronics Applications

Abstract: Electronics is a field of study ubiquitous in our daily lives, since this discipline is undoubtedly the driving force behind developments in many other disciplines, such as telecommunications, automation, and computer science. Nowadays, electronics is becoming more and more widely applied in life science, thus leading to an increasing interest in bioelectronics that is a major segment of bioengineering. A bioelectronics application that has gained much attention in recent years is the use of sensors for biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The accuracy for a presented solution was ±0.24 °C over a range of 20–55 °C. In [ 10 ], the authors indicated the possibility of using the IDC for sensing biological materials. Similarly, the substrate of the mentioned sensor was quartz and the components were made using microfabrication methods.…”
Section: Areas Of Microwave Applications In the Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy for a presented solution was ±0.24 °C over a range of 20–55 °C. In [ 10 ], the authors indicated the possibility of using the IDC for sensing biological materials. Similarly, the substrate of the mentioned sensor was quartz and the components were made using microfabrication methods.…”
Section: Areas Of Microwave Applications In the Microfluidicsmentioning
confidence: 99%
“…The use of microfluidic devices with integrated microwave components is notable mainly in biochemical and chemical applications, such as detecting the biological material [ 9 , 10 , 11 , 12 ]. Furthermore, due to the possibility of noncontact sensing and delivering the microwaves to the systems (using the antenna-based circuits), the possibilities are still increasing [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher width and gap between the sensing element fingers increases the sensing field lines through the MUT, which means a strong collaboration intervenes between MUT and resonator. 22 Sensitivity of the sensor can be improved via the optimization of different sensing elements, such as F w , F g , F L , and N E . The proposed design normalizes sensitivity can be estimated from the following Equation (4): 3…”
Section: Operation Principle and Design Simulationmentioning
confidence: 99%
“…Electro-magnetic (EM) wave biosensors are attracting a lot of attention due to multiple benefits, such as being minimally invasive and cost effective [19][20][21]. Recent advances in microwave sensing [22][23], together with other applications of microwaves in the frequencies [24][25][26], enable to explore new narrow band windows for membrane interactions research. Studies of the effects of a weak (non-thermal) microwave radiation on the cellular structures have clearly shown that the reaction of cells to weak microwave radiation is highly selective in frequency.…”
Section: Introductionmentioning
confidence: 99%